Sensorless Field Oriented Control of Induction Motor Drive using Extended Kalman Filter (EKF) - P, Riya Majeed; R, Vinod B. (2023 International Conference on Circuit Power and Computing Technologies (ICCPCT), 2023)
Electric machine operation depends heavily on control techniques, which have a direct impact on the performance of the entire system. Electric machines, which have significant effects on industrial development and human civilization, have been subject to a variety of control systems that have been tested and investigated. A diverse array of control techniques are employed, including Field Oriented Control (FOC), Direct Torque Control (DTC), and Fault Tolerant Control (FTC). In this scheme, the FOC technique is employed to regulate the speed of an Induction Motor (IM) drive and minimize fluctuations in torque. Field Oriented Control system for IM drive decouples flux and torque, resulting in shorter response times and, occasionally, simpler control actions. The model is validated using simulation studies in MATLAB/SIMULINK.